Exploring the Link between Uric Acid and Osteoarthritis - Ma, Cheryl Ann; Leung, Ying Ying (Frontiers in Medicine, 2017)
Both gout and osteoarthritis (OA) are common forms of arthritis that inflict a huge burden to an aging population with the increasing prevalence of obesity. Clinicians have long observed the link between these two conditions. In this review, we summarize the evidence from epidemiologic and immunological studies that described the possible relationship between the two conditions. The recent new understanding on monosodium uric acid crystal induced inflammation has given insight into probable shared pathogenesis pathways for both conditions. We describe the potential therapeutic implications, particularly regarding the possibility of repurposing traditional gout medications for use in OA.